Bond strength of artificial teeth attached to a microwave-polymerized denture base resin after immersion in disinfectant solutions - Pero, Ana Carolina [UNESP]; Scavassin, Priscila Mattos [UNESP]; Nunes, Élen Massaro [UNESP]; Policastro, Vivian Barnabé [UNESP]; Giro, Gabriela [UNESP]; Compagnoni, Marco Antonio [UNESP] (American College of Prosthodontists, 2015)
To evaluate the bond strength between two types of acrylic resin teeth and a microwave denture base resin after immersion in disinfectant solutions for 180 days. Eighty specimens made of acrylic resin teeth (Biotone and Biotone IPN) attached to a microwave polymerized denture base resin (Nature-Cryl MC) were divided into eight groups (n = 10) according to the treatment (distilled water-control, 2% chlorhexidine digluconate, 1% sodium hypochlorite and sodium perborate solution-Corega Tabs). The shear strength tests (MPa) were carried out using a universal testing machine with a 0.5 mm/min speed. Data analysis was performed using ANOVA and multiple comparison Student-Newman-Keuls post hoc test (α = 0.05). Biotone IPN showed similar results among the groups (distilled water, 8.25 ± 1.81 MPa; chlorhexidine, 7.81 ± 3.34 MPa; hypochlorite, 7.75 ± 3.72 MPa; and Corega Tabs, 7.58 ± 2.27 MPa, whereas Biotone showed significantly lower shear bond strength values for the groups immersed in Corega Tabs (5.25 ± 3.27 MPa) and chlorhexidine (6.08 ± 2.35 MPa). Soaking the dentures in 1% sodium hypochlorite could be recommended as a disinfectant solution for dentures fabricated with conventional acrylic resin denture teeth and microwave denture base resin. For dentures fabricated with IPN teeth and microwave denture base resin, all the soaking solutions evaluated in this study could be suggested to denture wearers.
Keywords: Artificial tooth; Denture bases; Denture cleansers; Shear strength